1995
DOI: 10.1007/bf00404705
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dry eye in Japanese eye centers

Abstract: Our findings suggest that dry eye is one of the most common ocular disorders encountered by physicians. Furthermore, if patients use VDTs or wear CLs, the likelihood of dry eye occurring is higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
104
2
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(120 citation statements)
references
References 13 publications
7
104
2
7
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][19][20][21] Studies that also involve tests of tear function including Schirmer's test, tear break-up time, fluorescein staining, or rose Bengal staining for determination of dry eye have found generally lower prevalence rates. 3,21 Limitations in comparisons of studies in different populations include different age distribution of the population, definitions of dry eye, or methodology. Most studies of dry eye have been confined to developed nations and older populations, with resultant lack of ethnic diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][19][20][21] Studies that also involve tests of tear function including Schirmer's test, tear break-up time, fluorescein staining, or rose Bengal staining for determination of dry eye have found generally lower prevalence rates. 3,21 Limitations in comparisons of studies in different populations include different age distribution of the population, definitions of dry eye, or methodology. Most studies of dry eye have been confined to developed nations and older populations, with resultant lack of ethnic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…These figures range from 14 to 34%. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][19][20][21] The published data regarding the relation between dry eye and gender are partially inconsistent. 22,23 The study performed in Australia by McCarty et al 3 [1][2][3][4][5][6][7] Each dry eye test that is frequently performed in clinical practice seeks only to measure a specific disorder of dry eye.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with other studies which have reported a higher prevalence of the dry eye in females than in males in the general population. 14,15 An association of dry eyes with postmenopausal females is well known. The results in our study may have been influenced by a larger number of males undergoing SICS as compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of dry eyes varies from 10.8% to 57.1% [2]- [6]. Several factors could cause this variation.…”
Section: Introductionmentioning
confidence: 99%
“…These include no standardization of the type of patients selected for the study, dry eye questionnaires, objective tests and dry eye diagnostic criteria. In literature there are various risk factors for dry eye which include air pollution, smoking, low humidity, high temperature, sunlight exposure and drugs [2] [7]- [11].…”
Section: Introductionmentioning
confidence: 99%